2022
DOI: 10.3389/fmed.2022.1057424
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut microbiome in the intergenerational transmission of the obesity phenotype: A narrative review

Abstract: Obesity is considered an epidemic by the World Health Organization. In particular, maternal obesity can affect the development of obesity and other related metabolic disorders in infants. Recently, both animal and human studies have pointed to the importance of the gut microbiome in facilitating the transmission of the obesity phenotype from mother to offspring. The gut microbiome changes significantly during the progression of pregnancy, and the microbiota of the amniotic fluid and placenta have recently been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
1
0
1
Order By: Relevance
“…Дети, рожденные путем операции КС, лишены контакта с микробиотой влагалища и фекалий матери, в результате наблюдаются отклонения в формировании микробиоты, особенно в первые месяцы жизни [11,12] Гастроэнтерология поверхностный полисахарид Bacteroides fragilis распознается Toll-подобными рецепторами 2-го типа (TLR-2), что запускает синтез интерлейкина-10 и других цитокинов, которые влияют на баланс Th1/Th2 и способствуют иммунотолерантности [13]. У детей, рожденных путем КС, наблюдается более высокий риск развития инфекционных и неинфекционных заболеваний, таких как аллергия, диабет, целиакия и ожирение [14][15][16][17][18].…”
Section: Discussionunclassified
“…Дети, рожденные путем операции КС, лишены контакта с микробиотой влагалища и фекалий матери, в результате наблюдаются отклонения в формировании микробиоты, особенно в первые месяцы жизни [11,12] Гастроэнтерология поверхностный полисахарид Bacteroides fragilis распознается Toll-подобными рецепторами 2-го типа (TLR-2), что запускает синтез интерлейкина-10 и других цитокинов, которые влияют на баланс Th1/Th2 и способствуют иммунотолерантности [13]. У детей, рожденных путем КС, наблюдается более высокий риск развития инфекционных и неинфекционных заболеваний, таких как аллергия, диабет, целиакия и ожирение [14][15][16][17][18].…”
Section: Discussionunclassified
“…Not only that, research has also demonstrated that the formation of the gut microbiome and metabolic health in infants, which is influenced by the mother’s HFD-induced obesity as well as environmental exposures, may play a role in the transmission of obesity and metabolic disorders from one generation to the next [ 85 , 86 ]. Although the impact of paternal gut dysbiosis and metabolic dysfunction on future generations remains unclear, this study would benefit from exploring the transgenerational effects of combined BPA exposure and TFD on the gut microbiome or metabolic health of subsequent generations.…”
Section: Discussionmentioning
confidence: 99%